1992
DOI: 10.1128/jb.174.16.5302-5308.1992
|View full text |Cite
|
Sign up to set email alerts
|

Electrogenic malate uptake and improved growth energetics of the malolactic bacterium Leuconostoc oenos grown on glucose-malate mixtures

Abstract: Growth of the malolactic bacterium Leuconostoc oenos was improved with respect to both the specific growth rate and the biomass yield during the fermentation ofglucose-malate mixtures as compared with those in media lacking malate. Such a finding indicates that the malolactic reaction contributed to the energy budget of the bacterium, suggesting that growth is energy limited in the absence of malate. An energetic yield (YATP) of 9.5 g of biomass mol ATP'1 was found during growth on glucose with an ATP producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
29
1

Year Published

1995
1995
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 30 publications
4
29
1
Order By: Relevance
“…This finding could be explained by the fact that citric acid (Lutgens and Gottschalk 1980;Marty-Teysset et al 1996), malic acid (Renault et al 1988;Loubiere et al 1992) and fumaric acid (Tran et al 1997;Tielens and Van Hellemond 1998) may positively modulate the energy metabolism of some bacterial strains usually residing in the hindgut. Lopez et al (1999) observed that sodium fumarate at 5 and 10 mmol L -1 was able to stimulate ruminal proliferation of cellulolytic bacteria and digestion of fiber.…”
Section: Discussionmentioning
confidence: 99%
“…This finding could be explained by the fact that citric acid (Lutgens and Gottschalk 1980;Marty-Teysset et al 1996), malic acid (Renault et al 1988;Loubiere et al 1992) and fumaric acid (Tran et al 1997;Tielens and Van Hellemond 1998) may positively modulate the energy metabolism of some bacterial strains usually residing in the hindgut. Lopez et al (1999) observed that sodium fumarate at 5 and 10 mmol L -1 was able to stimulate ruminal proliferation of cellulolytic bacteria and digestion of fiber.…”
Section: Discussionmentioning
confidence: 99%
“…The transmembrane pH and electrical gradients, e.g., ∆pH and ∆ψ, were measured by determining the internal to external gradient of 14 C-benzoic acid and 3 H-tetraphenylphosphonium bromide (TPP + ), respectively, after centrifugation of the cells through silicon oil, as previously described [13]. The ATPase activity was determined as previously described [5].…”
Section: Measurement Of ∆Ph and ∆ψ Values And Of Atpase Activitymentioning
confidence: 99%
“…Only at concentrations higher than 5 mM, the transport proceeded by a low-affinity uniport which was able to generate ⌬p. For L. oenos, three different models for L-malate uptake and ⌬p generation, all based on L-malate uniport, have been proposed (12,24,30 Other authors proposed simultaneous low-affinity H-malate Ϫ uniport and passive diffusion of nondissociated L-malate, the relative contribution being dependent on the external pH (30). In a previous report on studies in membrane vesicles (24), we proposed a model showing H-malate Ϫ uniport in the pH range 3 to 5.6 and at low concentrations of L-malate.…”
mentioning
confidence: 99%
“…Only at concentrations higher than 5 mM, the transport proceeded by a low-affinity uniport which was able to generate ⌬p. For L. oenos, three different models for L-malate uptake and ⌬p generation, all based on L-malate uniport, have been proposed (12,24,30). Loubiere et al suggested a system similar to that of L. plantarum, in which the combined action of H-malate Ϫ /H ϩ symport and H-malate Ϫ uniport depends on the external malate concentration (12).…”
mentioning
confidence: 99%
See 1 more Smart Citation